Use it or lose it: measuring trends in wild species subject to substantial use. Issue 3 (July 2014) - Tierney, Megan; Almond, Rosamunde; Stanwell-Smith, Damon; McRae, Louise; Zöckler, Christoph; Collen, Ben; Walpole, Matt; Hutton, Jon; de Bie, Steven
Abstract The unsustainable use of wild animals and plants is thought to be a significant driver of biodiversity loss in many regions of the world. The international community has therefore called for action to ensure the sustainable use of living resources and safeguard them for future generations. Indicators that can track changes in populations of species used by humans are essential tools for measuring progress towards these ideals and informing management decisions. Here we present two indicators that could be used to track changes in populations of utilized vertebrate species and levels of harvest sustainability. Preliminary results based on sample data both at the global level and for the Arctic show that utilized species are faring better than other species overall. This could be a consequence of better management of these populations, as indicated by more sustainable harvest levels in recent decades. Limitations of the indicators are still apparent; in particular, there is a lack of data on harvested populations of some vertebrate classes and from certain regions. Focusing monitoring efforts on broadening the scope of data collected and identifying interactions with other potential drivers of decline will strengthen these indicators as policy tools and improve their potential to be incorporated into future sets of indicators to track progress towards global biodiversity targets.